Exploring the In Vitro and In Vivo Therapeutic Efficacy of Juniperus oxycedrus Cade Oil: Antioxidant, Anti-inflammatory, and Anti-asthmatic Effects in an Allergic Asthma Model: Therapeutic Effects of Cade Oil in Allergic Asthma - Ahmida, Meryem; Zadam, Mustapha Hichem; Djaber, Nesrine; Khaldi, Taha; Bensouici, Chawki; Khattabi, Latifa; Amara, Hichem; Zaafour, Moncef; Boumendjel, Amel; Messarah, Mahfoud; Boumendjel, Mahieddine (Cellular and Molecular Biology, 2024)
This investigation aimed to explore the antioxidant, anti-inflammatory effects of Cade oil and its efficacy within a Wistar allergic asthma model. The antioxidant activity was assessed through various in vitro tests using chain-breaking antioxidant effects (radical scavenging and reducing abilities assays). In vivo experiments involved Wistar rats categorized into four groups: negative control group, Ovalbumin-sensitised/challenged group, Cade oil-treated group, and Ovalbumin-sensitised/challenged Cade oil-treated group. These experiments aimed to evaluate oxidative stress parameters in the lungs and erythrocytes. The results indicated that the Cade oil exhibited significant antioxidant capabilities, evidenced by its radical scavenging activity against DPPH, ABTS, and Galvinoxyl radicals, with IC50 values ranging from 21.92 to 24.44 µg/mL. Besides, the reducing abilities methods showed A0,5 value ranging from 11.51 to 30.40 µg/mL for reducing power, Cupric ion reducing antioxidant capacity, and O-phenanthroline assays. Additionally, the IC50 value for β-carotene scavenging was found to be (8.2 ± 0.25 µg/ml). Analysis revealed high levels of polyphenols and flavonoids in Cade oil, indicating rich polyphenol (275.21 ± 3.14 mg GAE/g DW) and flavonoid (28.23 ± 1.91 µg QE/mg) content. In vivo findings highlighted Cade oil’s efficacy in reducing inflammatory cell recruitment, enhancing antioxidant status, reducing lipid peroxidation, and improving histopathological alterations within the allergic asthma model. These results demonstrated that Cade oil has a potent antioxidant, anti-inflammatory, and anti-asthmatic properties, suggesting its potential therapeutic application in asthma treatment.